Pelatihan Kewirausahaan Pada Remaja Berbasis Marketing Mix di Desa Plupuh Sragen - Rizkiawan, Ilham Karin; Hadi, Fahman; Aisah, Nurul (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2024)
Entrepreneurship training based on the Marketing Mix was conducted to enhance the capacity of young entrepreneurs in Plupuh Village, Sragen, who exhibit high enthusiasm but lack adequate marketing knowledge. This activity was held from July 20 to August 25, 2024, with 15 participants aged 18–25 years engaged in the culinary and fashion sectors. Their businesses, generally running for 5 months to 2 years, often experienced instability. Through this program, participants received counseling and training on Marketing Mix strategies, covering product, price, promotion, place, people, process, and physical evidence. Additionally, the training included methods to create effective marketing content using social media platforms like Instagram and TikTok to expand market reach and increase brand awareness. The program outcomes indicated improved participant understanding of integrated marketing strategies. Participants were able to differentiate their products creatively and emphasize quality, making their businesses more competitive. By leveraging social media, these young entrepreneurs successfully expanded their market reach and strengthened their brand positioning within the community.